MENGGAGAS CONSTITUTIONAL COMPLAINT DI INDONESIA - Qurrata Ayuni (Widyariset, 2010)
In essence, constitution is the contract between state and its citizen. It’s declare the rights and duty amongthem. As the highest norm, constitution must be applied as it is written. To make sure that all of public decision orother positive law are always vis a vis to the constitution, it is need to put one of the authority to ConstitutionalCourt in Indonesia named constitutional complaint. Using qualitative and literature study methode this research istrying to compare the practical and theoreitical of the constitutional complaint in some counties and its possibilityto applied in Indonesia. As results, constitutional complaint is indeed can be strengthening the rights of citizen inIndonesia and also prospective to be a member of Constitutional Court authorities.